Requalificação urbana do Terminal Hidroviário de Manaus - Iranduba - Simões, Pedro Felipe Gonzaga (Brasil, 2025)
This Final Graduation Project seeks to study the Manaus-Iranduba Waterway Terminal (TEHMI), also known as Porto do São Raimundo, understanding its dynamics and functions in order to analyze and contextualize it from a more contemporary perspective, valuing the human scale of pedestrians, workers, visiting users and neighbors. Formulating a result based on the field analysis, photos and diagnostic maps that support a proposal for urban intervention to better qualify the natural and spontaneous vocations of TEHMI. Starting from a more sustainable urbanism and a more human scale, a possibility of walking through an area with a strong image over the Rio Negro, and a view of the Ponte Jornalista Phelippe Daou, also known as Ponte do Rio Negro, an urban area with priority for people who already use TEHMI not only as a port space, but also as a space for leisure and culture, based on the guidelines expressed in Jan Gehl's book, Cities for People. In the end, the result is a specific project that respects the current functioning and use of TEHMI.